Pengembangan Literasi Berbasis Kampung Pada Masyarakat Desa Bontobangun - Sri Satriani; Muh. Rizal Usman; Wahyuddin Wahyuddin (LPPM UNINUS, 2019)
Bontobangun Village is one of the villages in Bulukumba district, had several work programs developed to improve the quality of human resources, village development and to help government programs on a global scale. One of the programs they are working on is building a literacy spirit in the Bontobangun village community. The local government also has plans to create a place for developing village literacy such as reading park. However, the village govermment is still constrained by the problem of the concept of making a reading park, and funds to collect books to be stored in this reading park. In additional, the local government is also constrained by the lack of creative and innovative approaches to socializing this program and the lack of human resources who can manage the program so that it can be heard in the ears of the local community. So through all of the programs that are presented by KKN-PPM Muhammadiyah Universiy of Makasaar students by carring out the concept of village based literacy development, there are several work programs including one book one person movement aimed at helping the village government hold books for reading park collections originating from community donations, making reading park, literacy themed competitions for junior high school students, learning weeks activities for Bontobangun’s village children. These activities are expected to be the first solution to help the local government in realizing literacy awareness in Bontobangun village community. The implementation of this activity uses maximum of 2 months. Items of village based literacy development activities are sustainable will be submitted to village that have been formed to be followed up. While the activity in the form of learning weeks, competitions and the other activities are expected to be used as sample to organize more creative and innovative activities and can process on develop village literacy program in the future.